Divergence of functions and expression patterns of soybean bZIP transcription factors - Yue, Lin; Pei, Xinxin; Kong, Fanjiang; Zhao, Lin; Lin, Xiaoya (Frontiers in Plant Science, 2023)
Soybean (Glycine max) is a major protein and oil crop. Soybean basic re-gion/leucine zipper (bZIP) transcription factors are involved in many regulatory path-ways, including yield, stress responses, environmental signaling, and carbon-nitrogen balance. Here, we discuss the members of the soybean bZIP family and their classifica-tion: 156 members have been identified and clustered into 14 groups. Our review of the transcriptional regulation and functions of soybean bZIP members provides important information for future study of bZIP transcription factors and genetic resources for soy-bean breeding.